2020
DOI: 10.3390/diagnostics10030155
|View full text |Cite
|
Sign up to set email alerts
|

Elevated LysoGb3 Concentration in the Neuronopathic Forms of Mucopolysaccharidoses

Abstract: Mucopolysaccharidoses (MPSs) are a group of lysosomal storage disorders associated with impaired glycosaminoglycans (GAGs) catabolism. In MPS I, II, III, and VII, heparan sulfate (HS) cannot be degraded because of the lack of sufficient activity of the respective enzymes, and its accumulation in the brain causes neurological symptoms. Globotriaosylsphingosine (LysoGb3), the deacylated form of globotriaosylceramide (Gb3), is described as a highly sensitive biomarker for another lysosomal storage disease-Fabry d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Further longitudinal monitoring studies need to be performed in the future to ascertain whether the normal levels of lyso-Gb3 in some of these patients could be related to treatment response. This corroborates the findings of Baydakova et al (2020), who observed increased DBS lyso-Gb3 in neuronopathic forms of MPS (including MPS III) [ 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…Further longitudinal monitoring studies need to be performed in the future to ascertain whether the normal levels of lyso-Gb3 in some of these patients could be related to treatment response. This corroborates the findings of Baydakova et al (2020), who observed increased DBS lyso-Gb3 in neuronopathic forms of MPS (including MPS III) [ 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…Neurofibrillary light chain is significantly elevated in cerebrospinal fluid (CSF) and serum of MPS II patients with neurological involvement, and they are positively correlated with CSF HS, which can be used to assess neuronal health and damage in treated MPS II patients [ 8 ]. Lysozyme B3 has been found to be a potential secondary biomarker of nervous system involvement in MPS patients [ 6 , 72 ]. Elevated expression of three candidate biomarkers, matrix metalloproteinase 19, α-trypsin interinhibitor heavy chain 3, and α-1-microglobulin, was demonstrated in MPS I cartilage, and serum abundance of these molecules was found to correlate with MRI and histologic degeneration grading [ 92 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…The principal biochemical abnormality caused by the NAGLU gene or activity deficiency in MPS IIIB is the accumulation of lysosomal HS (the mechanism of HS storage has not yet been fully understood) and the elimination of this polysaccharide, or fragments derived from it, in body fluids [63]. Additionally, secondary storage products, such as: GM 2 and GM 3 gangliosides that play a role in central nervous systems pathology [63,77], inflammatory cytokines, reactive oxygen species [78] and globotriaosylsphingosine (LysoGb3) [79] have also been described. There are hypotheses concerning secondary storage product accumulation.…”
Section: Mucopolysaccharidosis Type Iiibmentioning
confidence: 99%
“…There are hypotheses concerning secondary storage product accumulation. Some have argued that this phenomenon may be due to the inhibition of relevant lysosomal enzymes by HS/GAGs, which when accumulating can selectively bind various hydrolases causing a decrease in their activity [79]. Others claim that they can cause critical disruption of the internal environment of the lysosome (for example, by changes in pH) and thus lead to reduced degradation of additional substrates [80].…”
Section: Mucopolysaccharidosis Type Iiibmentioning
confidence: 99%